Cybersecurity Regulations for Protection and Safeguarding Digital Assets (Data) in Today’s Worlds - Naeem AllahRakha (Universitas Negeri Semarang, 2024)
This paper examines cybersecurity regulations and practices for safeguarding digital assets like data in today's interconnected landscape. As cyber risks flourish, comprehensive frameworks outlining technical, administrative, and legal protocols are vital for securing critical systems and sensitive information. The paper's background emphasizes rising digitization, surging threat sophistication, and necessitating diligent governance. Its objectives include analyzing prominent regulations and highlighting principles around confidentiality, integrity, and availability. The qualitative study adopts a doctrinal approach and grounded theory analysis to methodically assess prominent legislation. The paper discusses legislative developments in domains like breach disclosure, identity authentication, and encryption methodologies that strengthen cyber resilience. It suggests reconciling compliance complexity through oversight alignment. The paper concludes by underscoring the need for positive incentives and public-private partnerships that collectively enhance cyber hygiene. It recommends consistent interpretation and proactive investments in capacity building to secure our deepening digital economy against exponentially evolving threats.